2013
DOI: 10.1016/j.jjie.2013.01.004
|View full text |Cite
|
Sign up to set email alerts
|

What does a temporary help service job offer? Empirical suggestions from a Japanese survey

Abstract: The aim of this paper is to test whether or not a temporary help service (THS) job benefits workers in Japan. By applying the average treatment effect on the treated estimation and its sensitivity tests to the Japanese survey data, we obtained the following findings. First, we observed evidence that THS work negatively impacts the probability of permanent employment in subsequent waves, when compared to directly hired part-time employment. Second, THS workers earn a significantly higher hourly wage than those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Dispatched workers are persons employed by temporary worker agencies who are sent to firms on a fixedterm basis. See Okudaira, Ohtake, Kume and Tsuru (2013) for an in-depth analysis of the role of temporary work agencies in Japan.…”
mentioning
confidence: 99%
“…Dispatched workers are persons employed by temporary worker agencies who are sent to firms on a fixedterm basis. See Okudaira, Ohtake, Kume and Tsuru (2013) for an in-depth analysis of the role of temporary work agencies in Japan.…”
mentioning
confidence: 99%
“…Okudaira et al . () investigated the effect of being a dispatch employee on the probability of entering regular employment and concluded that employment through a dispatch agency is not a stepping stone to regular employment. Although not investigated in their study, this leaves open the possibility that introduction of the law may have increased the amount of non‐standard employment in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Our ATT results indicate that the TAW experience leads to a less smooth transition to regular employment and longer periods of non-regular employment, compared to other non-regular workers with no experience in the TAW sector. Okudaira et al (2013) found that, in comparison to directly hired part-time workers, temporary workers have a higher probability of becoming unemployed in the subsequent waves of their survey. Based on these findings, it appears that the TAW employment does not equate to termination of one's unemployment status.…”
Section: -A Estimation With Childhood Time Preferencementioning
confidence: 92%
“…A few studies have empirically examined the function of temporary work toward regular employment in Japan. Notably, Okudaira et al (2013) investigated the empirical effect of temporary help service work on the probability of obtaining permanent employment or becoming unemployed in the subsequent waves of their survey, using the data from an Internet survey conducted in Japan from 2008 to 2011. Their findings suggest that temporary work may not have any ''stepping stone'' effect on the permanent employment.…”
Section: Introductionmentioning
confidence: 99%